Características morfogênicas, estruturais e produtivas do capim-piatã em sistemas de integração lavoura-pecuária-floresta no cerrado - Santos, Valéria Ana Corvalã dos (2011)
Technologies have been developed for use efficient and sustainable of earth. The integrated crop-livestock-forest systems coming is presentation advantage an alternative. But There is a conceptual deficit in interpreting results research on the morphogenetic characteristics and structural changes related to the productivity of forage plants and animal. This that background, was conducted experiment at EMBRAPA - Beef Cattle, Campo Grande, MS, during the period November 2010 to March 2011, in order to study the morphogenetic characteristics, structure and accrual herbage of Brachiaria brizantha cv. BRS Piatã, and the to put on of heifers nelore in integrated crop-livestock-florest system in Cerrado. The experimental was a randomized complete block design with two replications. Treatments were blueprint arranged in split plot, being that the plot corresponded to production systems and the subplots, the heights of the grass residue Piatã (0.15 and 0.30). The systems were: crop-livestock integration (ILP), integrated crop-livestock-forest with 357 trees / ha - 14 m spacing between rows of and 2 m between trees (iLPF-1) - and integrated crop-livestock-forest with 227 trees / ha - 22 m spacing between rows of and 2 m between trees (iLPF-2). The tree component was composed for of hybrid H-13 of Eucalyptus ((Eucalyptus urograndis). The morphogenetic and structural characteristics were evaluated in tillers per experimental unit in the understory, a period of 28 days, in intervals 3 or 4 days, at the end of the period was held counting the number of tillers, of january on february the 2011. The mass forage production is to assess across close cut when soil, and live weight gain of the heifers by half weighing of animals on each 28 days when, in experiment period. After cutting, the samples were weighed and separate into the components of the tiller: leaf, stem with sheath and dead material, and the weeds. The forage chemical composition was obtained by Spectroscopy of near infrared reflectance (NIRS). Shade caused an increase of leaf and stem elongation rates. Shading levels have not influenced leaf appearance rates and leaf number per tiller. No went difference found between the systems for the morphogenetic and structural traits and dry matter production. Pasture traits, and live weight gain did not vary with the systems. However, improve the shading the property chemical-bromatologic of grass-piatã. There effect in the heights in grazing forage mass, 2,648 and 2,066 kg ha-1; crude protein, 7.74 and 10.7 %; in acidic detergent fiber, 40.08 and 39.25%; high and low respectively. Moderate shading in ILPF did not affect pasture traits, support of capacity and live weight gain of the heifers, in comparison to the values obtained for an ILP pasture. Piatã-grass presents phenotypical plasticity and responded the shade conditions; therefore, it has a good potential to be used in systems integrated crop-livestok-florest.